A kind of iron-phosphorus composite material with slow release of ferrous iron and its preparation method and application

The iron-phosphorus composite material with sustained release of ferrous ferrous prepared by ball milling solves the problems of wastewater and soil repair of composite heavy metals, and achieves efficient repair of hexavalent chromium, copper and zinc, which is stable, environmentally friendly and economical. Advantages.

CN115739927BActive Publication Date: 2025-02-07CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211421267.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-14
Publication Date
2025-02-07
Estimated Expiration
2042-11-14

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively solve the problem of repairing wastewater and soils of composite heavy metals, especially the composite pollution of hexavalent chromium, copper and zinc. The preparation process of traditional restoration materials is complex, costly and poor repair efficiency.

Method used

The ball milling method is used to mix the reducing iron powder with the phosphorus-containing industrial by-product to form a sustained release of ferrous ferrous composite material. This material promotes the reduction of hexavalent chromium by forming Cu-Fe primary cells in situ, and forms insoluble substances with copper and zinc, thereby achieving the fixation and stabilization of composite heavy metals.

Benefits of technology

This method achieves efficient repair of composite pollution of chromium, copper and zinc, with good material stability, green and environmentally friendly, no secondary pollution, simple application method and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115739927B_ABST
    Figure CN115739927B_ABST
Patent Text Reader

Abstract

The invention discloses an iron-phosphorus composite material capable of slowly releasing ferrous iron, and a preparation method and application thereof. Reducing iron powder and phosphorus-containing industrial byproducts are mixed and placed in a ball mill for ball milling, and the repair material is obtained by sieving after the reaction. The material can slowly release active ferrous iron, reduce highly toxic hexavalent chromium to low-toxic trivalent chromium, and the hexavalent chromium removal rate can reach 100%. Moreover, divalent metal cations such as copper and zinc can be fixedly adsorbed at the same time, and the removal rate can reach more than 99%. The "galvanic cell effect" generated by the in-situ adsorption of copper, zinc, etc. on the surface of the material to form a "quasi-bimetal" with iron is utilized to accelerate the reduction of hexavalent chromium. The material preparation method of the invention is simple, low-cost, and easy to prepare on a large scale, and can solve the problem of hexavalent chromium, copper, zinc, and other multi-metal composite pollution of wastewater or soil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the technical field of environmental green restoration materials and their preparation and application, and relates to an iron-phosphorus composite material with slow-release ferrous iron and its preparation method and application, which is suitable for the treatment and restoration of wastewater and soil contaminated by hexavalent chromium, copper, zinc, cobalt, nickel and other heavy metals. Background technology:

[0002] The wastewater generated by ore mining, electroplating industry, and metal smelting processes often contains a complex and diverse mixture of heavy metal ions, which is manifested as the coexistence of anionic hexavalent chromium and cationic heavy metals (such as copper, zinc, cobalt, nickel, etc.). At the same time, the disorderly discharge and leakage of industrial wastewater, as well as the illegal stacking of metal slag, have caused a large amount of toxic and harmful heavy metals to invade the soil and groundwater in the factory and surrounding areas, causing serious pollution.

[0003] Hexavalent chromium exists in the form of anions in water and soil media, and is often detoxified by reduction to low-toxic trivalent chromium, while copper and zinc exist in the form of cations and can be treated by adsorption and fixation. Zero-valent iron is considered to be a very promising material for repairing hexavalent chromium pollution. However, the physicochemical characteristics of zero-valent iron itself make its surface easily passivated. Therefore, the development of modified zero-valent iron with high activity and high stability is a current research hotspot. Industrial phosphogypsum is accumulated in large quantities in industrial production. It is cheap and easy to obtain. It is a heavy metal pollution remediation material with good application prospects. However, the remediation effect of unmodified phosphorus-containing industrial by-products is not ideal. Acidity and alkalinity and calcium content are important factors affecting its remediation effect on copper and zinc pollution.

[0004] Traditional single heavy metal element or single group remediation materials are difficult to solve the problem of complex pollution of multiple heavy metals in wastewater and soil. In addition, existing remediation materials still have some shortcomings, such as complex preparation process, high cost, secondary pollution and poor remediation efficiency. Among them, iron-based bimetallic materials designed to improve the remediation efficiency, on the one hand, generally introduce precious metals, which are costly, and the preparation process is complex and energy-intensive; on the other hand, the introduction of the second metal has the risk of leaching. Therefore, it is necessary to develop a remediation material that can simultaneously enhance the remediation effect of single reduced iron and phosphorus-containing industrial by-products, achieve simultaneous fixation of chromium, copper, and zinc composite metals, and can generate elemental copper in situ in wastewater to form a green and environmentally friendly iron-based bimetallic material. Summary of the invention:

[0005] The primary purpose of the present invention is to provide a method for preparing a slow-release ferrous iron-phosphorus composite material, which is suitable for the repair of chromium-copper-zinc composite polluted water and soil, has good fixing and repairing effect, good stability, is green and has no secondary pollution, and has a simple application method.

[0006] The iron-phosphorus composite material for slow-release ferrous iron provided by the present invention comprises Fe(0) and Fe(II) for reducing Cr(VI), Cu(II) and Zn(II), wherein Fe(II) has a slow-release effect; Fe(OH) for stabilizing Cr(III), Cu and Zn 3 ; Used to stabilize PO of Cu and Zn in water or soil 4 3- ; and the "quasi-bimetallic" formed by the in-situ adsorption of copper, zinc and other substances on the surface of the material during the treatment of wastewater contaminated by complex heavy metals. The method uses reduced iron as the iron source and phosphorus-containing industrial byproducts as the phosphorus source; the two are mixed and placed in a ball mill for ball milling.

[0007] The advantages of this synthesis method are: (1) the average particle size is smaller after ball milling, and a large number of nano-scale amorphous zero-valent iron particles are attached to the surface of phosphorus-containing industrial by-products, which increases the specific surface area, thereby increasing the reaction active sites and greatly improving the reaction activity; (2) the ball milling method can significantly affect the particle size of phosphorus-containing industrial by-products, and at the same time can significantly increase the reaction activity of phosphorus-containing industrial by-products, that is, increase the effective phosphorus content; (3) part of the oxide layer on the surface of the reduced iron is replaced by phosphate, and more iron ions are dissolved during the reaction, and there is the ability to continuously release iron ions; (4) in copper-containing composite polluted wastewater, a copper-iron primary battery is formed in situ, which accelerates the release of iron ions and promotes the fixation and stabilization of chromium, copper, and zinc ions.

[0008] A method for preparing an iron-phosphorus composite material for slow-release ferrous iron comprises the following steps: mixing reducing iron powder with phosphorus-containing industrial byproducts, ball-milling the mixture, and then sieving the mixture to obtain the obtained material.

[0009] In the method for preparing the iron-phosphorus composite material with slow-release ferrous iron, the added reducing iron powder includes: iron powder or industrial iron filings, preferably with a mesh size of 100.

[0010] The method for preparing a slow-release ferrous iron-phosphorus composite material, wherein the phosphorus-containing industrial byproduct comprises P 2 O 5 More than 17% of phosphorus-containing industrial by-products, further including P 2 O 5 The mass fraction of industrial phosphogypsum and / or industrial phosphate rock is greater than 17%, preferably passing 100 mesh.

[0011] In the method for preparing the iron-phosphorus composite material with slow-release ferrous iron, the mass ratio of reducing iron powder to phosphorus-containing industrial by-products is 4:1 to 2:3, preferably 3:2 to 2:3.

[0012] The mass ratio of the above-mentioned reduced iron powder and phosphorus-containing industrial by-products has a very important influence on the effect of the product of the present invention in removing heavy metals. When the mass ratio of reduced iron powder to phosphorus-containing industrial by-products is within the range of 4:1 to 2:3, the removal rate of Cr(VI) and Cu(II) and Zn(II) of the prepared material is greater than that of the reduced iron powder and phosphorus-containing industrial by-products after mechanical ball milling activation alone, indicating that the composite degree of iron powder and phosphorus-containing industrial by-products within this mass ratio range is better than that of other mass ratios. It can be seen from the SEM images within different mass ratios that, relative to the materials prepared with other mass ratios, when m(iron powder: phosphate rock powder) = 3:2, more nano-scale fine particles adhere to the surface of the phosphate rock powder, which greatly increases the specific surface area and reaction activity of the particles. The nano-scale fine particles include but are not limited to zero-valent iron.

[0013] In the method for preparing the iron-phosphorus composite material with slow-release ferrous iron, during the ball milling preparation process, the reaction time is 1 to 5 hours, preferably 2 to 4 hours, and more preferably 2 hours.

[0014] In the method for preparing the iron-phosphorus composite material with slow-release ferrous iron, during the ball milling preparation process, the rotation speed of the ball mill is 250 to 400 rpm, preferably 350 rpm.

[0015] In the method for preparing the slow-release ferrous iron-phosphorus composite material, during the ball milling preparation process, the mass ratio of the ball milling balls to the added materials is 10:1 to 50:1, preferably 40:1 to 50:1, and more preferably 40:1.

[0016] The ball milling is preferably performed using an omnidirectional planetary ball mill, and the grinding balls and the ball milling jar are preferably made of hard stainless steel. A vacuum environment is maintained during the ball milling preparation process.

[0017] The second object of the present invention is to provide an iron-phosphorus composite material with slow-release ferrous iron obtained by the above preparation method.

[0018] The third object of the present invention is to provide an application of the slow-release ferrous iron-phosphorus composite material, specifically for repairing water bodies or soils contaminated by complex heavy metals.

[0019] Furthermore, the heavy metal includes: one or more of hexavalent chromium, copper and zinc.

[0020] Specific application method: chromium-copper-zinc composite polluted wastewater is added with the iron-phosphorus composite material of the invention that slowly releases ferrous iron. During the treatment process, a Cu-Fe primary battery is formed in situ on the surface of the material, which accelerates the release of active Fe(II), quickly reduces Cr(VI) to Cr(III) and forms (Cr x Fe 1-x )(OH) 3 precipitation, while promoting the removal of heavy metal cations.

[0021] The chromium-copper-zinc composite contaminated soil is added with the slow-release ferrous iron-phosphorus composite material of the present invention, and then deionized water is added, with a mass ratio of soil: composite material of reduced iron and phosphorus-containing industrial by-products: water = 100: (1-5): 50, mixed evenly, and the treatment time is at least 7 days.

[0022] The present invention is innovative in that while selecting phosphorus-containing industrial byproducts, it also adds reduced iron powder, and the surface oxide layer of the reduced iron is partially oxidized by PO 4 3- Replacement, forming a material that continuously releases active Fe(Ⅱ). On the one hand, it avoids the agglomeration of zero-valent iron after ball milling, and on the other hand, mechanical activation promotes the release of effective phosphorus from phosphorus-containing industrial byproducts. At the same time, in the presence of Cu(Ⅱ) in the composite polluted wastewater, a Cu-Fe primary battery is formed on the surface of the material in situ, which promotes the reduction of Cr(VI). At the same time, the reduced Cr(Ⅲ) and Fe(Ⅱ) can form insoluble substances with Cu(Ⅱ) and Zn(Ⅱ). Impurities in phosphorus-containing industrial byproducts also have a certain adsorption effect on heavy metal ions.

[0023] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:

[0024] 1. The invention provides a method for preparing an economical and easy-to-prepare heavy metal contaminated wastewater and soil remediation material, wherein the main raw material, phosphorus-containing industrial byproduct gypsum, is piled up in large quantities, which not only occupies a large amount of land, but also causes severe environmental problems; phosphorus-containing industrial byproduct ore is cheap and easy to obtain, and is a heavy metal pollution remediation material with good application prospects. Using phosphorus-containing industrial byproduct gypsum as a raw material is expected to solve its storage problem. The material preparation method is simple, low-cost, and easy to prepare on a large scale, and is suitable for actual heavy metal pollution, especially the remediation of chromium-copper-zinc composite contaminated wastewater and soil.

[0025] 2. The present invention promotes the release of effective phosphorus in phosphate fertilizer and the corrosion of the surface of reduced iron. Part of the oxide layer on the surface of reduced iron is replaced by phosphate, more iron ions are dissolved during the reaction, and the iron ions can be continuously released.

[0026] 3. The present invention uses high-energy ball milling to closely combine the two raw materials and synergistically remove the composite heavy metal ions. The surface of the material after ball milling is rough and the particle size is reduced. At the same time, by adjusting the ratio of reduced iron and phosphate rock powder, many nano-scale fine particles are adhered to the surface of the phosphate rock powder, making the zero-valent iron evenly distributed and reducing its agglomeration.

[0027] 4. The present invention can more effectively solve the problem of composite heavy metal pollution. In a hexavalent chromium pollution system in which cations represented by copper and zinc exist, the reduced iron and phosphate fertilizer composite material can promote the reduction of hexavalent chromium and improve the removal rate. The copper ions are reduced to copper element, forming numerous tiny copper-iron primary cells in situ, which has the strongest effect on the removal of hexavalent chromium.

[0028] 5. The composite material containing reduced iron and phosphorus-containing industrial byproducts synthesized by the present invention is an environmentally friendly fixative, and its main components are iron and phosphate. Phosphate can improve the physical and chemical properties of soil and increase soil fertility. During application, it will not destroy the structural properties of the soil, has little effect on the pH value of the soil, will not cause soil acidification problems, and avoids the risk of secondary pollution. Description of the drawings:

[0029] Figure 1 (a) SEM image, (b) element mapping, (c) EDS image of the iron-phosphorus composite material with slow-release ferrous iron using phosphate rock (PR) as raw material of the present invention;

[0030] Figure 2 The FTIR spectrum of the iron-phosphorus composite material with slow-release ferrous iron using phosphate rock powder (PR) as raw material of the present invention;

[0031] Figure 3 XRD patterns of materials with different ZVI / PR mass ratios prepared by the method of Example 1;

[0032] Figure 4 The effect of materials with different ZVI / PR mass ratios prepared by the method of Example 1 on the removal of Cr(VI);

[0033] Figure 5 The removal effects of materials with different ZVI / PR mass ratios prepared by the method of Example 1 on Cr(VI), Cu(II) and Zn(II) composite ions are shown in (a) after 30 min of reaction, (b) after 2 h of reaction, and (c) after 24 h of reaction.

[0034] Figure 6 The removal effect of the repair material of Example 1 of the present invention on Cr(VI), Cu(II) and Zn(II) in a multi-ion coexistence system;

[0035] Figure 7 The comparison of the removal effect of the repair material of Example 1 of the present invention on Cr(VI) in the presence of Cu(II) or Zn(II) is shown;

[0036] Figure 8 The effect of the repair material of Example 1 of the present invention on removing Cr(VI) at different Cu(II) concentrations;

[0037] Fig. 9 The Tafel scanning curves of Cu(0) deposited on the repair material of Example 1 of the present invention under different Cu(II) immersion times;

[0038] Fig.10 The removal effect of materials with different ZVI / PR mass ratios prepared by the method of Example 1 on total Cr(VI) in chromium-contaminated soil;

[0039] Fig.11 The removal effect of the remediation material of Example 1 of the present invention on the effective Cr(VI) (a), Cu(II) (b) and Zn(II) (c) in the composite contaminated soil;

[0040] Fig.12 This is the change curve of Fe(II) released into the soil by the repair material of Example 1 of the present invention at different repair times. Specific implementation method:

[0041] The following specific examples are used to illustrate the preparation method of a slow-release ferrous iron-phosphorus composite material involved in the present invention and its application in the treatment of wastewater contaminated by multiple heavy metals and soil remediation, which will not constitute a limitation to the present invention.

[0042] Example 1

[0043] 3g of reduced iron powder and 2g of phosphate rock powder (the chemical composition and percentage of phosphate rock powder are shown in Table 1) are sieved through a 100-mesh sieve and placed in a stainless steel vacuum ball mill at the same time. Grinding balls with a ball-to-material ratio of 40:1 are added, the stainless steel ball mill is sealed, and the air in the stainless steel ball mill is evacuated using a water pump. After solid-phase ball milling for 2 hours at room temperature 25°C and a rotation speed of 350r / min, the mill is taken out and the ball mill is reversed every 30 minutes, for a total of 2 hours of clockwise ball milling and 2 hours of counterclockwise ball milling. Collect the ball-milled samples, and then sieve them through a 100-mesh sieve to obtain the repair material. The dried samples are then vacuum-sealed and stored. The SEM images, EDS images, and FTIR spectra are shown as follows, respectively. Figure 1 and Figure 2 In the infrared spectrum of phosphate rock powder, the -1 (v 3 ) and 1050-1100cm -1 (v 2 ) were found in both split absorption bands of PO 4 3- Ions exist. OH - Ion stretching absorption band (v 1 =3540cm -1 ) means the presence of crystal structure water. PO was found in the prepared material. 4 3-The antisymmetric stretching vibration absorption band of ions indicates that PO 4 3- Smoothly introduced into the material surface.

[0044] Table 1. Chemical composition and percentage of phosphate rock powder

[0045]

[0046] Example 2

[0047] On the basis of Example 1, by controlling the mass ratio of reduced iron powder (ZVI) and phosphate rock powder (PR), many tiny particles are attached to the surface of the phosphate rock powder, which greatly increases the specific surface area and reaction activity of the particles. Figure 1 The XRD spectrum of the material obtained after high-energy ball milling activation modification is shown in Figure 3 Fe appears at 2-Theta of 44.5° and 64.5° (JCPDS NO.06-0696) 0 As the mass of iron increases from 1g to 3g, Fe 0 The characteristic peak of PR only appears when the mass ratio of ZVI / PR is 1:4, and does not appear in other ratios. When ZVI / PR=4:1, due to Fe 0 The content of Fe is too high, which aggravates the 0 The agglomeration effect of ZVI / PR is not significant. 0 The characteristic peak is most obvious, and the activity of zero-valent iron is highest at this time.

[0048] Example 3

[0049] 0.1 g of the material with different ZVI / PR mass ratios prepared by the method of Example 1 was used to treat 100 mL of Cr(VI) solution with a concentration of 50 mg / L. The reaction was shaken in an oscillator at a medium speed for 24 h and then sampled. The concentration of Cr(VI) was determined by diphenylcarbazide spectrophotometry. The removal rate of chromium by the material prepared in Example 1 showed a pendulum-like shape, among which the ZVI / PR mass ratios of 3:2, 1:1, and 2:3 had better effects, all of which could reach more than 50%. Figure 4 .

[0050] Example 4

[0051] 0.2g of the material with different ZVI / PR mass ratios prepared by the method of Example 1 was used to treat 100mL of a solution containing chromium, copper and zinc. The initial concentrations of the three heavy metals were 50mg / L, 100mg / L and 50mg / L, respectively. Under medium-speed oscillation in an oscillator, samples were taken at three time points: 30min, 2h and 24h of reaction. The concentration of hexavalent chromium was determined by diphenylcarbazide spectrophotometry, and the concentrations of copper and zinc in the solution were determined by inductively coupled plasma emission spectrometry. After 24h, the material prepared by the mass ratio of Example 1 could achieve a removal rate of more than 99% for chromium, copper and zinc. During the reaction process, after 30min, the composite material can completely remove hexavalent chromium; after 2h, the composite material can completely remove copper. Figure 5 .

[0052] Example 5

[0053] 0.2 g of the ZVI / PR material prepared in Example 1 was used to treat 100 mL of a solution containing chromium, copper and zinc. The initial concentrations of the three heavy metals were 50 mg / L, 100 mg / L and 50 mg / L, respectively. The reaction was shaken at a medium speed in an oscillator for 24 hours. Samples were taken 12 times within 24 hours. The concentration of hexavalent chromium was determined by diphenylcarbazide spectrophotometry. The concentrations of copper and zinc in the solution were determined by inductively coupled plasma emission spectrometry. The removal effect of the material in Example 1 on Cr(VI) and cationic metals in a multi-ion coexistence system was as follows: Figure 6 .

[0054] Example 6

[0055] A hexavalent chromium solution with a concentration of 50 mg / L was added to three 100 mL small white bottles, and then a copper solution with a concentration of 50 mg / L and a zinc solution with a concentration of 50 mg / L were added to two of the small white bottles, and 0.2 g of the material prepared in Example 1 was added to each small white bottle for treatment. The three small white bottles and their parallel groups were oscillated at a medium speed in an oscillator for 24 hours, and samples were taken 12 times within the time period. The hexavalent chromium concentration in the filtrate was determined by diphenylcarbazide spectrophotometry, and the concentrations of copper and zinc were determined by inductively coupled plasma emission spectrometry. The removal rate of Cr(VI) in the coexistence system (75.32%-97.08%) was higher than that of the single Cr(VI) system (69.94%). The divalent metal cations represented by copper and zinc promoted the removal of hexavalent chromium, among which copper ions had the strongest promoting effect on the removal of hexavalent chromium, which was 1.08-1.39 times that of the single Cr(VI) system. Figure 7 .

[0056] Example 7

[0057] Different copper ion concentration gradients were set: 0 mg / L, 10 mg / L, 20 mg / L, 30 mg / L, 50 mg / L, and 100 mg / L. A hexavalent chromium solution with a concentration of 50 mg / L was added thereto respectively, and 0.2 g of the material prepared in Example 1 was used for treatment. The small white bottle was shaken in an oscillator at a medium speed for 30 minutes to take a sample. The hexavalent chromium concentration in the filtrate was determined by diphenylcarbazide spectrophotometry, and the copper concentration was determined by inductively coupled plasma emission spectrometry. As the copper ion concentration increased, the material's removal effect on hexavalent chromium gradually increased. The best effect was achieved when the copper ion concentration was 100 mg / L, which could reach 93.39%. Figure 8 .

[0058] Example 8

[0059] Collect the samples immersed in Cu 2+ The ZVI / PR material prepared in Example 1 in the solution was scanned for Tafel corrosion curve. Fig. 9 The free corrosion potential of the ZVI / PR material is -0.45 V, and the corrosion potential further decreases with the increase of immersion time. When the immersion time is 3 h, the corrosion potential is -0.95 V. This 500 mV corrosion potential confirms that Cu 0 The deposited ZVI / PR exhibits significantly different corrosion behavior and has stronger electron transfer capability.

[0060] Example 9

[0061] For the remediation of the contaminated soil of the Changsha Chromium Salt Factory, the total hexavalent chromium content in the soil was 407.25 mg / kg. After adding 5% of the materials prepared in different proportions according to the method of Example 1 of the present invention, samples were taken after 10 days. The removal rate of the total hexavalent chromium is shown in the attached Fig.10 After 10 days, the material prepared according to Example 1 of the present invention reduced the total hexavalent chromium content in the soil to 3.9 mg / kg, with a removal rate of 99.04%. The repair material has a good removal effect on hexavalent chromium in the soil.

[0062] Example 10

[0063] For the remediation of contaminated soil in electroplating sites, the total hexavalent chromium content in the soil was 154.5 mg / kg, and the effective copper, zinc and hexavalent chromium contents were 38.6 mg / kg, 145.8 mg / kg and 149.5 mg / kg, respectively. After adding 1%, 3% and 5% of the material prepared in Example 1 of the present invention, samples were taken after 1d, 3d, 7d, 14d and 28d. The change trends of effective hexavalent chromium and cationic metal ions are shown in the attached Fig.11After 28 days, the total hexavalent chromium content in the soil dropped to 1.2 mg / kg, and the effective copper, zinc, and hexavalent chromium contents were 17.1 mg / kg, 53.9 mg / kg, and 0 mg / kg, respectively. The remediation material has a good removal effect on hexavalent chromium in the soil, and has a good fixation effect on effective copper and zinc.

[0064] At the same time, the Fe(Ⅱ) content in the soil sampled after 1d, 3d, 7d, 14d and 28d was determined. The trend of the change is shown in the attached Fig.12 The content of Fe(Ⅱ) in the soil generally showed a slow upward trend. After 28 days, the content of Fe(Ⅱ) in the soil was: 5% dosage > 3% dosage > 1% dosage, which confirmed that the material has the property of slowly releasing Fe(Ⅱ) in the soil.

Claims

1. A method for preparing an iron-phosphorus composite material for slow-release ferrous iron, characterized in that: The reduced iron powder is mixed with industrial phosphate rock, ball-milled and then sieved to obtain the product; The reducing iron powder is iron powder with a mesh size of 100 or industrial iron filings; The industrial phosphate rock has a mesh size of 100 and a P2O5 mass fraction greater than 17%; The mass ratio of reduced iron powder to industrial phosphate rock is 3:2 to 2:3; The ball milling synthesis process was carried out in a vacuum ball milling tank, and the ball milling speed was 250-400 rpm; The mass ratio of grinding balls to added materials is 40:1 to 50:1; During the ball milling synthesis process, the ball milling time is 2 to 4 h; The product after ball milling was sieved through a 100-mesh sieve; By adding reduced iron powder, part of the oxidation layer on the surface of the reduced iron powder is oxidized by PO4 3- By adjusting the ratio of reducing iron powder to industrial phosphate rock, nano-scale fine particles adhere to the surface of the phosphate rock powder after ball milling of the industrial phosphate rock, the zero-valent iron is evenly distributed and its agglomeration is reduced.

2. An iron-phosphorus composite material for slow-release ferrous iron, characterized in that: Prepared by the method described in claim 1.

3. Use of the iron-phosphorus composite material with slow-release ferrous iron according to claim 2 in wastewater or soil contaminated by heavy metals.

4. The use according to claim 3, characterized in that: Including wastewater or soil polluted by hexavalent chromium, copper, zinc and other metals.

Citation Information

Patent Citations

  • Heavy metal-polluted acid soil modifying agent and application thereof

    CN105419806A

  • Zero-valent iron-mineral composite material with high reduction activity and preparation method therefor

    CN110498494A

  • Soil remediation agent with ardealite as base material as well as preparation method and application of soil remediation agent

    CN115466622A